Capital punishment on trial: Furman v. Georgia and the death penalty in modern America - Oshinsky, David M. (Landmark law cases & American society, 2010)
"I didn't intend to kill nobody" -- "I am n-n-not dying" -- "Struck by lightning" -- "Death is different" -- "Let's do it" -- The "mirror test" -- "The machinery of death